Site-directed mutation of β-galactosidase from Streptococcus thermophilus for galactooligosaccharide-enriched yogurt making - J.C. Zhao; Y.L. Mu; X.Y. Gu; X.N. Xu; T.T. Guo; J. Kong (Journal of Dairy Science, 2022)
ABSTRACT: β-Galactosidase is one of the most important enzymes used in dairy processing. It converts lactose into glucose and galactose, and also catalyzes galactose to form galactooligosaccharides (GOS), so-called prebiotics. However, most of the β-galactosidases from the starter cultures have low transgalactosylation activities, the process that results in galactose accumulation in yogurt. Here, a site-directed mutation strategy was attempted, to genetically modify β-galactosidase from Streptococcus thermophilus. Out of 28 Strep. thermophilus strains, a β-galactosidase gene named bgaQ, encoded for high β-galactosidase hydrolysis activity (BgaQ), was cloned from the strain Strep. thermophilus SDMCC050237. It was 3,081 bp in size, with 1,027 deduced amino acid residuals, which belonged to the GH2 family. After replacing the Tyr801 and Pro802 around the active sites of BgaQ with His801 and Gly802, the GOS synthesis of the generated mutant protein BgaQ-8012 increased from 20.5% to 26.7% at 5% lactose, and no hydrolysis activity altered obviously. Subsequently, the purified BgaQ or BgaQ-8012 was added to sterilized milk inoculated with 2 starters from Strep. thermophilus SDMCC050237 and Lactobacillus delbrueckii ssp. bulgaricus ATCC11842. The GOS yields with added BgaQ or BgaQ-8012 increased to 5.8 and 8.3 g/L, respectively, compared with a yield of 3.7 g/L without enzymes added. Meanwhile, the addition of the BgaQ or BgaQ-8012 reduced the lactose content by 49.3% and 54.4% in the fermented yogurt and shortened the curd time. Therefore, this study provided a site-directed mutation strategy for improvement of the transgalactosylation activity of β-galactosidase from Strep. thermophilus for GOS-enriched yogurt making.